2010
DOI: 10.1111/j.1365-246x.2010.04702.x
|View full text |Cite
|
Sign up to set email alerts
|

Depths to the magnetic layer bottom in the South China Sea area and their tectonic implications

Abstract: S U M M A R YThe depths to the magnetic layer bottom (Z b ) in the South China Sea (SCS) area are estimated by computing radially averaged amplitude spectra of total field magnetic anomalies. We test different sizes of moving windows in which the spectra are calculated to better understand how window sizes affect the depth estimations. Apart from lowering the resolutions of estimated Z b , larger windows do not necessarily incur presumable increases in Z b in the SCS area. Although the centroid method is taken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
0
8

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 65 publications
(152 reference statements)
6
69
0
8
Order By: Relevance
“…One of the methods for examining the thermal structure of the crust is the estimation of the CPD using aeromagnetic data (Smith et al, 1977;Okubo et al, 1985Okubo et al, , 1989Okubo et al, , 1994Okubo et al, , 2003Tsokas et al, 1998;Tanaka et al, 1999;Stampolidis and Tsokas, 2002;Dolmaz et al, 2005;Ates et al, 2005;Aydin et al, 2005;Qingqing et al, 2008;Li et al, 2010;Li, 2011;Bilim, 2011;Manea and Manea, 2011;Abd El Nabi, 2012;Hisarli et al, 2012;Saleh et al, 2013;Sayed et al, 2013;Abraham et al, 2014;Obande et al, 2014;Starostenko et al, 2014). Various studies have shown correlations between Curie temperature depths and average crustal temperatures, leading to viable conclusions regarding lithospheric thermal conditions in a number of regions around the world (Ross et al, 2006;Rajaram, 2007;Bouligand et al, 2009).…”
Section: Centroid Depth Methods For Calculating Dbms 221 Random Magmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the methods for examining the thermal structure of the crust is the estimation of the CPD using aeromagnetic data (Smith et al, 1977;Okubo et al, 1985Okubo et al, , 1989Okubo et al, , 1994Okubo et al, , 2003Tsokas et al, 1998;Tanaka et al, 1999;Stampolidis and Tsokas, 2002;Dolmaz et al, 2005;Ates et al, 2005;Aydin et al, 2005;Qingqing et al, 2008;Li et al, 2010;Li, 2011;Bilim, 2011;Manea and Manea, 2011;Abd El Nabi, 2012;Hisarli et al, 2012;Saleh et al, 2013;Sayed et al, 2013;Abraham et al, 2014;Obande et al, 2014;Starostenko et al, 2014). Various studies have shown correlations between Curie temperature depths and average crustal temperatures, leading to viable conclusions regarding lithospheric thermal conditions in a number of regions around the world (Ross et al, 2006;Rajaram, 2007;Bouligand et al, 2009).…”
Section: Centroid Depth Methods For Calculating Dbms 221 Random Magmentioning
confidence: 99%
“…A multilayer situation is seen in the analysis of windows 1, 6, 7, 8, 12, 13, 14, and 15. by enlarging the window, long wavenumber components and/or spectra of uniformly magnetized layer could also gain more portions of power, enough to disguise the peak on the amplitude spectrum (Li et al, 2010). The shape of the radial power spectrum as calculated in previous studies ideally should display a peak at low wavenumbers.…”
Section: Application To Magnetic Datasetmentioning
confidence: 99%
“…As shown by a recent study, the uppermost mantle can be magnetized by in-situ serpentinization caused by infiltration of seawater through large transform faults [109]. In the SCS, Curie isotherm is recently found to lie underneath the Mohorovicic discontinuity [110], hence raising the question whether the uppermost mantle here is also magnetized because of serpentinization. Before the origin of magnetism in the uppermost mantle is found, we need to investigate first the sub-surface liquid activities in the SCS and their impacts by testing against the above hypothesis [111].…”
Section: Hydrothermal and Cold Seep Serpentinization Gas Hydratesmentioning
confidence: 99%
“…It indicates that the heat flows are likely more influenced by thermal conductivity. Previous studies on the eastern and southeastern Asia, the north Atlantic and the South China Sea show that the low thermal conductivity of crustal rocks may induce a delay between the changed thermal field and the effect of heat flow [47,[73][74]. It is supposed that the low thermal conductivity might probably cause the low CPD with low heat flow in the Eastern Yunnan Block.…”
Section: Cpd Versus Heat Flowmentioning
confidence: 99%